Methodology for venous outflow assessment during ultrasound of extracranial vessels: status of the problem - N. V. Korneeva; M. A. Lovrikova; K. V. Zhmerenetsky (Кардиоваскулярная терапия и профилактика)
The article focuses on important issues of methodology for studying venous outflow from the head and neck, emphasizing the importance of this problem for early diagnosis due to the long-term asymptomatic course of venous circulation disorders. The features of the head and neck venous circulation are presented. We outlined the difficulties in studying venous outflow in the clinic. The results of Russian and foreign studies on venous outflow assessment using various methods are presented, while attention is focused on non-invasive diagnostics using ultrasound. In addition, we present our original research data on venous outflow assessment during verticalization in patients with internal carotid arterial stenosis.